PERAN KOMPETENSI GURU PAI DALAM MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DI SMP ISLAM SIROJUL MUNIR AL IHSAN MELINTING - Rofiqul Wahid (UNISAN JURNAL, 2024)
The mark of this investigation is to look at the particular employment of teachers’ master capacities in additional creating student learning about Islamic Severe Preparation (PAI) and spreading the practicality of the use of information development as a learning resource in student learning in PAI subjects. . The investigation strategy used is library research, explicitly assembling and separating information from various sources with respect to the subject. Considering data revelations in the field and as gotten a handle on in the past parts, a couple of finishes can be attracted concerning the meaning of the issue raised in this assessment. These issues are according to the accompanying: Considering the results of the composing focus on that has been finished, it will in general be contemplated that the occupation of PAI teacher capable capacity is fundamental in additional creating student learning achievement in PAI subjects. PAI teachers who have good capacity can offer a better development chance than students. Beside that, the use of information development as a learning resource can moreover additionally foster student learning brings about PAI subjects. Information development can make it more direct for students to get to information and engage them to progress independently and naturally. Consequently, to additionally foster student learning achievement in PAI subjects, it is recommended that PAI teachers cultivate better capable capacities and use information as a convincing learning resource. This should chip away at the idea of PAI learning and augmentation reality in the modernized period